Asset purchase programmes and financial markets: lessons from the euro area - Carlo Altavilla; Giacomo Carboni; Roberto Motto (European Central Bank (ECB), 2015)
We evaluate the effects on asset prices of the ECB asset purchase programme (APP) announced in January 2015 and assess its main transmission channels. We do so by first extending a term structure model with bond supply effects to account for assets with different types of risk premia. We then derive model-based predictions for cross-asset price movements associated with the transmission channels identified in the model. We finally validate empirically these predictions by means of an event- study methodology, reaching the following conclusions: The impact of the APP on asset prices is sizeable albeit the programme was announced at a time of low financial distress. This may appear puzzling in light of existing literature that finds a large impact of asset purchases only in periods of high financial distress. Consistent with the model, we explain this apparent puzzle by showing how the low financial distress, while indeed weakening certain transmission channels, has reinforced other channels because of its interplay with the asset composition of the programme. Targeting assets at long maturity and spanning the investment-grade space have supported the duration and the credit channels. At the same time, the low degree of financial stress prevailing at announcement of the programme, while weakening the local supply channel, has facilitated spill-overs to non-targeted assets.
Keywords: E43; E44; E52; E58; E65; G14; 330; APP; Event study; LSAP; Quantitative Easing; Yield curve